TINJAUAN HUKUM BISNIS : PERLINDUNGAN HUKUM TERHADAP PERUSAHAAN TRADER DALAM PENGANGKUTAN DAN PENJUALAN BIJIH NIKEL - Oetomo, Farhan Setyo (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Nickel ore trading companies face various obstacles in the nickel ore trading process. One of the main problems is the difference in nickel content analysis results between the loading port and the unloading port, which is caused by the discrepancy in the survey results from independent surveyors. This difference has a significant impact because nickel content is the main determinant in determining selling and buying prices. In addition, the uncertainty of the origin of nickel ore, where miners often get nickel ore from outside the relevant IUP location so that the legality of nickel ore is questionable. Another risk arises from the transportation aspect, because shipping nickel ore by sea using barges is considered high risk. On the other hand, the implementation of Circular Letter (SE). Ministry of Energy and Mineral Resources (ESDM). WNomorW3 E/MB.01/DJB/2022W which requires buying and selling transactions to use the Free on Board (FOB) scheme is also an additional challenge for traders, because the risk of goods is transferred to the buyer after the loading process. In dealing with these various risks, adequate business legal protection is needed, both through contract arrangements, protection of trader rights, and dispute resolution mechanisms to provide certainty, fairness, and security in nickel ore buying and selling transactions. Keywords: Nickel Ore Trader, Nickel Ore Surveyor, Free On Board (FOB)